Multiplex paper-based designs for point-of-care (POC) diagnostics - Seth, Misago; Buza, Joram (International Journal of Research in Medical Sciences, 2017)
Background: Accurate and timely diagnosis is usually the first step towards appropriate disease management. In resource-limited settings, healthcare workers lack proper facilities to perform vital tests, and the diagnosis of disease is often determined by non-specific, physiological symptoms alone. Simple and rapid tests are needed as prerequisite tools for patient care and must conform to the criteria set out by the World Health Organization. To address the challenge of specific diagnosis for diseases that present with similar symptoms, multiplex diagnostic platforms must be designed. Methods: Simple designs for multiplexed paper-based diagnostic platforms were developed. Laser cutting and wax printing were used to create specific patterns on paper to guide the flow of sample and reagents towards reaction zones. Multi-arm and single strip multiplex platforms were designed and tested using Human Immunoglobulin G, Hepatitis B virus surface antigen (HBsAg), and Helicobacter pylori antigens. Results: All designs produced promising results with the lowest limit of detection for antigens being 30ng/ml for single strip designs. Conclusions: The use of glass fibre conjugate pad was found to be more sensitive compared wax-printed chromatography paper. Results from this study indicate great potential for further application in development of diagnostic low-cost paper-based diagnostic devices.